Elagolix as GnRH antagonist in controlled ovarian stimulation for intrauterine insemination - Munmun, Sadia Afrin; Sultana, Nighat; Yasmin, Mahamuda; Akhter, Dilruba; Ishrat, Shakeela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Controlled ovarian stimulation with gonadotropins may be complicated by premature luteinizing hormone surge and premature luteinization. Premature LH surge and premature luteinization can be inhibited by GnRH antagonists so that gonadotropin stimulation can be extended, enabling the appropriate development of more than one follicle. Elagolix is an oral GnRH antagonist used in treatment of endometriosis. Elagolix, like injectable GnRH antagonists, may be applied for preventing premature luteinization. Objective was to compare the effects of elagolix with no elagolix on preventing premature luteinization in ovarian stimulation with intrauterine insemination, on the day of trigger. Methods: This quasi-experimental study was conducted on a total of 60 infertile women selected for ovarian stimulation and intrauterine insemination. The women were given ovarian stimulation with tab letrozole and injectable gonadotropins. Transvaginal ultrasound for folliculometry was done from day 8 onwards. When the leading follicle was at least 14 mm, the women were assigned into two groups. Elagolix 150 mg once daily was added and continued to the day of trigger in the intervention group. Patients in the control group did not receive elagolix as described above. Premature LH surge (serum LH≥10) and premature luteinization (serum LH≥10 IU/l and serum progesterone ≥1 ng/ml) were assessed on the day of trigger. Results: Twenty-six women in the elagolix group and 26 in the control arm completed the study. There was total absence of premature LH surge and premature luteinization in the elagolix group as compared to the 30.8% and 23.1% respectively in the control group. There was no statistically significant difference in clinical pregnancy rates. Conclusions: Elagolix, an oral GnRH antagonist, when applied to controlled ovarian stimulation for intrauterine insemination, eliminate premature luteal surge and premature luteinization. But there is no improvement in clinical pregnancy rate.